2016
DOI: 10.1016/j.cgh.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Anti-TNF-α Therapy: Serum Levels of Infliximab and Adalimumab Are Associated With Mucosal Healing in Patients With Inflammatory Bowel Diseases

Abstract: In a retrospective study, we found significant association between serum levels of anti-tumor necrosis factor agents and level of mucosal healing. We propose that serum levels of 6-10 μg/mL for infliximab and 8-12 μg/mL for adalimumab are required to achieve mucosal healing in 80%-90% of patients with IBD, and that this could be considered as a "therapeutic window." Exceeding these levels produces only a negligible gain in proportion of patients with mucosal healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
269
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(286 citation statements)
references
References 30 publications
14
269
2
1
Order By: Relevance
“…An IFX level above 5 µg/ml [area under the curve (AUC) = 0.75, p < 0.0001] and an ADA level above 7.1 µg/ml (AUC = 0.7, p = 0.004) had a specificity of 85% for achieving mucosal healing. [Ungar et al 2015b]. Interestingly, the gained benefit from increasing the drug level achieved a plateau (for IFX levels above 8 µg/ml were associated with only minimal additional gain in mucosal healing, while the correlation between higher ADA levels and increased mucosal healing rate reached a plateau at 12 µg/ml).…”
Section: Immunopharmacological Predictorsmentioning
confidence: 92%
“…An IFX level above 5 µg/ml [area under the curve (AUC) = 0.75, p < 0.0001] and an ADA level above 7.1 µg/ml (AUC = 0.7, p = 0.004) had a specificity of 85% for achieving mucosal healing. [Ungar et al 2015b]. Interestingly, the gained benefit from increasing the drug level achieved a plateau (for IFX levels above 8 µg/ml were associated with only minimal additional gain in mucosal healing, while the correlation between higher ADA levels and increased mucosal healing rate reached a plateau at 12 µg/ml).…”
Section: Immunopharmacological Predictorsmentioning
confidence: 92%
“…Only limited data are available regarding the relationship of adalimumab concentrations, and antibodies to adalimumab [ATA], with favourable clinical outcomes and specifically with mucosal healing. 4,5,6,7 Based on these preliminary data, higher adalimumab levels and absence of ATA during maintenance therapy are associated with mucosal healing in IBD [ Tables 1 and 2 with a combined accuracy of 81.7% when based on the previously described cut-off of 4.9 μg/ml. 4,7 This, along with data from other recent studies, suggests that a threshold of 4.9 μg/ml may not be sufficient to achieve mucosal healing or deep remission.…”
mentioning
confidence: 91%
“…Exposure-response studies of anti-TNF therapy, based on therapeutic drug monitoring [TDM], show that favourable therapeutic outcomes, such as mucosal healing, are associated with high serum drug concentrations and undetectable anti-drug antibodies. 3,4,5,6,7,8,9 However, the majority of these studies, as well as two recently published meta-analyses, refer mainly to infliximab. 3,4,5,6,7,8,9,10,11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of aTNF-ab was greater in patients with no mucosal healing [67]. The recently published study by Ungar et al [68] confirmed this relationship between drug levels and mucosal healing in Crohn's disease.…”
Section: Since the Accent I (A Crohn's Disease Clinical Trial Evaluatingmentioning
confidence: 79%